UCZENIE SIĘ JĘZYKÓW OBCYCH W PROCESIE SAMODOSKONALENIA I ROZWOJU KOMPETENCJI TWÓRCZYCH - Blachowska-Szmigiel, Marzena (Neofilolog, 2018)
The purpose of this article is to present the learning foreign languages as an activity supporting the self-improvement and the development of creative competences. The article consists of three parts. The subject of the first part is an evolution of the concept of creativity, characteristics of the research paradigms of creativity and links between the self-improvement and the creative competences. The focus of the second part is neurobiological and intrapsychic basis for self-improvement and development of creative competences. The third part shows the benefits resulting from the activity of learning foreign languages in the context of self-improvement and development of creative competences.